Pemberdayaan UMKM Tradisional Budin Keripik melalui Digital Branding di Desa Tempel Jaya - Hayrasyirah Ryazinharwa; Sherly Putri Revika; Fadli Febriansyah Zen; Khalishah Khirman Fadhilah; Nabilah Ramadhani; Yusniah Yusniah (BADAN PENERBIT STIEPARI PRESS, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar of the Indonesian economy, yet they often face significant constraints in marketing and branding, especially in rural areas with limited access. Reliance on traditional word-of-mouth promotion leads to a narrow market reach and low product competitiveness. This community service activity aims to empower the